Gut microbiota dysbiosis in people living with HIV who have cancer: novel insights and diagnostic potential - Xie, Zhiman; Huang, Qianqian; Wen, Lemin; Luo, Tingyan; Ai, Sufang; Ruan, Guangjing; Liu, Ningmei; Wei, Yiru; Lan, Yingji; Cui, Ping; Cao, Qin; Liang, Hao; et al. (Frontiers in Immunology, 2025)
BackgroundPeople living with HIV(PLWH) are a high-risk population for cancer. We conducted a pioneering study on the gut microbiota of PLWH with various types of cancer, revealing key microbiota.MethodsWe collected stool samples from 54 PLWH who have cancer (PLWH-C), including Kaposi’s sarcoma (KS, n=7), lymphoma (L, n=22), lung cancer (LC, n=12), and colorectal cancer (CRC, n=13), 55 PLWH who do not have cancer (PLWH-NC), and 49 people living without HIV (Ctrl). The gut microbiota in fecal samples was analyzed using 16S rRNA sequencing. We compared the microbial diversity among groups and identified key microbiota and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways using random forest. Furthermore, we analyzed the correlation between microbiota and KEGG pathways and constructed microbiota Receiver Operating Characteristic (ROC) diagnostic models.ResultsCompared with PLWH-NC and Ctrl, PLWH with any type of cancer exhibited significantly lower alpha diversity and significant alterations in beta diversity of the gut microbiota. The significantly decreased abundance of Bacteroides and Bacteroides vulgatus in PLWH-C showed a negative correlation with the Pathways in cancer pathway, and a positive correlation with Choline metabolism in cancer, Central carbon metabolism in cancer, and Proteoglycans in cancer pathways. Bacteroides (AUC≥0.84) and Bacteroides vulgatus (AUC≥0.78) exhibited discriminatory diagnostic capabilities for PLWH-C in patients with different cancers compared with PLWH-NC and Ctrl.DiscussionWe confirmed a more severe dysbiosis of the gut microbiota in PLWH with KS, L, LC, or CRC. Bacteroides may be associated with disruptions in cancer-related metabolic pathways and serve as diagnostic biomarkers for PLWH with various cancers.